2019
DOI: 10.3390/pathogens8030109
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Combined Commercialized Ophthalmic Solutions Against Acanthamoeba Strains

Abstract: Acanthamoeba is a free-living amoebae genus which is present worldwide in natural and artificial environments. These amoebae are clinically important as causative agents of diseases in humans and other animals such as a fatal encephalitis or a sight threatening Acanthamoeba keratitis (AK). Lately; studies have focused on the search of novel therapeutic options for AK but also to prevent infections. Furthermore; the evaluation of commercialized products seems to be an option for this case since not clinical ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a previous work, we have demonstrated the effect of Naviblef® Daily Care foam to inhibit Acanthamoeba spp . ( Reyes-Batlle et al, 2019 ). This action could be results of the presence of Tea tree oil (TTA); in fact, for its antiseptic effect against bacteria, fungi and viruses, this component has been widely used in many eye cleanser and eyelid shampoo ( Mohammadpour et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work, we have demonstrated the effect of Naviblef® Daily Care foam to inhibit Acanthamoeba spp . ( Reyes-Batlle et al, 2019 ). This action could be results of the presence of Tea tree oil (TTA); in fact, for its antiseptic effect against bacteria, fungi and viruses, this component has been widely used in many eye cleanser and eyelid shampoo ( Mohammadpour et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we have demonstrated in vitro the efficacy of Naviblef® Daily Care foam to inhibit Acanthamoeba spp . ( Reyes-Batlle et al, 2019 ). In the present study, the effect of Belcils® as foam was evaluated against Acanthamoeba spp .…”
Section: Introductionmentioning
confidence: 99%
“…Given its pathogenic characteristics ( 24 ), studies with the genotype T4 often compare the virulence of clinical and environmental strains to understand the mechanisms involved during infection, invasion, and damage to the host tissues. The environmental strain known as Neff (ATCC 30010) is a widely used reference for characterizing virulence factors expressed by clinical isolates ( 25 ) and serves as a host model for interaction studies and the characterization of amoeba-resistant microorganisms, which encompass numerous important human pathogens, including the bacteria Legionella pneumophila , fungus from the genus Fusarium sp. and viruses such as adenoviruses and rotaviruses ( 3 , 5 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other corneal disorders such as the dry eye syndrome, is other disease derived from the use of contact lenses. Lately, diverse research studies have reported the efficacy of commercialized eye drops and ophthalmic solutions used for these other epithelial disorders, against the two life cycle stages of Acanthamoeba strains ( Sifaoui et al, 2017 , 2018 , 2020a , b ; Reyes-Batlle et al, 2019 ). Several commercialized ophthalmic solutions present preservatives such as Propylene Glycol, Benzalkonium chloride (BAK) or its derivatives such as POLYQUAD®, which have demonstrated antimicrobial ( Kinnunen et al, 1991 ; Nalawade et al, 2015 ) or anti- Acanthamoeba activity ( Sunada et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%